‘It’s not God I’m joking about’: Religion, stand-up comedy, dark comedy, and public sphere - Muhammad Farhan Hawari; Karunia Haganta; Firas Arrasy (SIMULACRA: JURNAL SOSIOLOGI, 2022)
This article tries to look at the social aspects of dark comedy used in stand-up comedy. Dark comedy is seen as problematic because it is in a vortex of humor, subjectivity, and the public. To capture and analyze these various phenomena, the authors use socio-anthropological perspective with the play theory from Sastramidjaja’s dissertation (2016) which is complemented by publicness from Sasono’s PhD theses (2019). This research is qualitative, using data collection methods in the form of semi-structured interviews with several main questions which are deepened by still referring to the main questions, especially to know the process of preparing jokes and stand-up comedy performances.This research was conducted in the Stand Up Indo Bekasi community and the Stand Up University Bhayangkara Jaya (UBJ) Bekasi with three comedians who often used dark joke material consisting of Bilal (Muslim), Ahmad (Muslim), and James (son of a Christian priest). This paper reveals the finding that dark comedy does not only come from the comedians, but also involves the public sphere as a form of grievances. The authors see that dark comedy is born from concerns that include comedian subjectivity in viewing various symbols – including religious symbols or those related to religion, reversing them, and contextualizing them in an incongruity.